Dietary rapeseed oil affects the expression of genes involved in hepatic lipid metabolism in Atlantic salmon (Salmo salar L.) - Jordal, Ann-Elise O; Torstensen, Bente E; Tsoi, Stephen; Tocher, Douglas R; Lall, Santosh P; Douglas, Susan E (American Society for Nutritional Sciences, 2005)
Supplies of marine fish oils (FO ) are limited, and sustainable production in aquaculture dictates that alternatives, such as vegetable oils, must be found that do not compromise fish health and product quality. Nutrigenomics is anticipated to provide an increased understanding of how nutrition influences metabolic pathways and homeostatic control, and may be used to measure and validate subtle changes in organ-specific, metabolic gene expression signatures. We have compared two groups of Atlantic salmon fed diets containing 100% FO or 75% rapeseed oil (RO)/25% FO for 42 weeks. A small-scale cDNA microarray was constructed to screen for changes in expression of lipid metabolism genes in the liver resulting from this partial substitution of RO for FO. Fatty acid desaturase gene expression was significantly increased in fish fed 75% RO compared to fish fed the control diet; this was confirmed by quantitative Real Time PCR analysis (Q-PCR). In addition, several genes, among these mitochondrial proteins, peroxisome proliferator activated receptor-γ (PPARγ) as well as other transcription factors, co-activators and signal transducers, showed significant differential regulation. This partially validated microarray may be used for further gene expression profiling using other dietary comparisons.